Oral modifications and clinical presentation due to Covid-19 in oncological patients (Research, Society and Development, 2022)
Covid-19, originated in December 2019, spread rapidly through China, becoming a public emergency. Patients diagnosed with cancer are considered a highly vulnerable group due to their  immunosuppressive condition caused by oncological treatment, therefore, this research aims to describe the clinical presentations and oral alterations in cancer patients diagnosed with Covid-19. It is a cross-sectional study with 20 oncology patients hospitalized with Covid-19. Oncological data, presence of comorbidities and symptoms related to Covid-19 were collected, and a clinical examination of the oral cavity was performed throughout the hospitalization, in order to identify oral changes. Results: The mean age of the patients was 53 years and the majority were female. Solid tumors represented 90%, the uterus being the most frequent region. Most patients were not under cancer treatment at the time of contamination (50%). Systemic arterial hypertension was the most frequent comorbidity (30%), followed by Diabetes Mellitus (25%). No patient was admitted to the ICU or required mechanical ventilation, the average length of stay was 13 days and all were hospital discharged. Cough and hypogeusia were among the most frequent symptoms. Hyposalivation and fungal infection were the most frequently observed oral alterations. Conclusion: The oral changes presented in oncological patients are in line with the findings of the literature, while the clinical presentation was contrary to the evidence that points to the oncological disease as a factor suggestive of a worse clinical condition in the face of Covid-19.